RESEARCH OF STEM EDUCATION IMPLEMENTATION IN UKRAINE: GENDER ASPECT - Buturlina, Oksana; Lysokolenko, Tetiana; Dovhal, Serhii (Educological discourse, 2021)
Given the importance of overcoming the shortage of staff in the STEM market, this study aims to present the analysis in terms of gender characteristics that affect the choice of profession by high school students. The sociological survey was conducted using the online method - a survey using Google Forms service. Four hundred and thirty-one respondents were 11th grade students (including 230 girls and 201 boys) who studied in experimental secondary schools in Dnipropetrovsk region participated in the survey. The methodology covers such aspects, as students’ knowledge of mathematics and natural sciences; career interests in the context of students’ motivation in studying STEM disciplines; students’ knowledge of the requirements for STEM careers. In the research, by comparing the answers of male and female respondents, it became possible to draw parallels on gender differences in the field of professional preferences of the surveyed students in the context of STEM education. Thus, after conducting research on gender specifics that influence the choice of profession in STEM areas by high school students, we can talk about the following. The obtained results show that there are insignificant differences between girls and boys in the field of interest in natural and mathematics sciences and technological education with an advantage in favor of boys. The results suggest that the choice of profession by high school students in the field of STEM is influenced by awareness of the prospects of the future career and self-confidence, which is connected with students’ academic success in mathematics, science and technology education. The study is one of the pilot projects in Ukraine. To further delve into the problem, it is necessary to conduct a regression analysis of several variables, in particular, the study of the relationship between career planning in the field of STEM and the type of residence of students (metropolis, city, town, village) and analysis of STEM preferences with reference to academic success of boys and girls.